If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(15x + 25) = 650 Reorder the terms: 5(25 + 15x) = 650 (25 * 5 + 15x * 5) = 650 (125 + 75x) = 650 Solving 125 + 75x = 650 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-125' to each side of the equation. 125 + -125 + 75x = 650 + -125 Combine like terms: 125 + -125 = 0 0 + 75x = 650 + -125 75x = 650 + -125 Combine like terms: 650 + -125 = 525 75x = 525 Divide each side by '75'. x = 7 Simplifying x = 7
| 72a^6-24a^8=0 | | 2x^3+x^2-9x+18=0 | | S^3+27=0 | | 3x-1=7x+15+2x | | -2(p-5)+3p=12 | | .60(10n-3)=1.5(n+2)-0.3 | | 8x-5=-141 | | 8x+7z+6y=0 | | y=|1+1| | | 0.5x-6=0.2x | | 400=200-25K | | 6(x-6)=6(x+10) | | y=|0+1| | | y=|-1+1| | | .3+3c=6.09 | | 3(x-1)-x=1 | | y=|-2+1| | | 3x^2-24x=-6 | | 90=4(2l+2w) | | -43=9x+2 | | -8x-4=10x+14 | | -15=4x+6 | | -4+2(0)=4 | | 17-10x+45=-6x-10+4 | | 6x+6h=14 | | 12-4(2p-1)=48 | | 3(x-2)=-2x+24 | | 8x+9=63 | | 180-x=6(90-x) | | 2x+4(x-1)=32 | | 2j=92.6 | | 4x+3=4-(4x-5) |